Protocolo para controle de dor pós-operatória em cirurgia periodontal: revisão sistemática e metanálise - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
Postoperative pain results from the combination of cognitive and pathophysiological phenomena. Under this perspective, the perception of pain is subjective so its control must take into account the individuality of each patient. Considering pain management options, there are pharmacological and non-pharmacological techniques to ease this postoperative discomfort, including postoperative pain after periodontal surgeries. Literature presents trials with specific treatments for pain control after periodontal surgery considering mild to moderate levels of pain often presented by patients undergoing this type of intervention. Hence, this dissertation was divided into two chapters. The first chapter refers to a literature review, which depicts some possibilities of analgesic intervention, as well as the perception of postoperative pain in periodontal surgery in the context of socio-demographic factors. The second chapter includes a systematic review and meta-analysis, investigating the effectiveness of preoperative and postoperative pharmacological analgesia protocols in periodontal surgery. The application of pharmacological control, both oral and topical, use of lasotherapy and also mechanical barriers in the postoperative period of patients undergoing periodontal surgery is current. In addition, pre- and postoperative analgesia protocols have similar effectiveness when oral analgesics and anti-inflammatory drugs are used. Thus, this paper compiles information of practical and clinical application in order to assist the dental surgeon in choosing methods of postoperative analgesia in periodontal surgery.
Keywords: Periodontia; Analgesia; Dor Pós-Operatória; Revisão Sistemática; Metanálise; Periodontics; Analgesia; Postoperative Pain; Systematic Review; Meta-Analysis; CNPQ::CIENCIAS DA SAUDE